Assurance Practices for Ethical and Sustainable Business Practices - Sari, Ratna (Advances in Managerial Auditing Research, 2024)
The purpose of this study is to examine the role of assurance practices in promoting ethical and sustainable business conduct within contemporary organizations. Through a qualitative research design and methodology, the study systematically analyzes existing literature to identify key insights and trends in assurance practices related to business ethics and sustainability. Findings indicate that assurance mechanisms, such as external audits and third-party certifications, play a crucial role in bolstering stakeholders' confidence in corporate disclosures concerning ethical conduct and sustainability performance. Additionally, the study highlights the evolving nature of assurance practices, particularly in response to emerging challenges and opportunities in the realm of business ethics and sustainability. Implications of the findings suggest that organizations can leverage assurance practices to enhance transparency, accountability, and trustworthiness, thereby fostering a culture of integrity and responsible conduct. Furthermore, the integration of technology and the expansion of assurance services offer opportunities to strengthen the effectiveness and relevance of assurance practices in addressing contemporary sustainability challenges.